The hidden/flying dragon : an exploration of the Book of Changes (I Ching) in terms of Nietzsche’s philosophy - Goosen, Daniel P. (Danie) (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2009.